2011
DOI: 10.1074/jbc.m111.252932
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin E2 Induces Matrix Metalloproteinase 9 Expression in Dendritic Cells through Two Independent Signaling Pathways Leading to Activator Protein 1 (AP-1) Activation

Abstract: Background:The signaling mechanisms involved in PGE2-induced MMP-9 expression in DCs are unknown. Results: PGE2-induced MMP-9 expression is mediated through the EP2/EP4 3 cAMP 3 PKA/PI3K 3 ERK signaling pathway. Conclusion: PGE2-induced ERK activation is required for the binding of AP-1 to the MMP-9 promoter. Significance: ERK inhibitors can be used to regulate DC migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(65 citation statements)
references
References 45 publications
4
61
0
Order By: Relevance
“…Interestingly enough, it has been recently reported that PGE2 induces MMP-9 expression in dendritic cells and that PGE2-induced MMP-9 is required for dendritic cells migration in vivo and in vitro (58). All together, these findings indicate the existence of a close bidirectional association between some MMPs and PTGS2.…”
Section: Discussionsupporting
confidence: 49%
“…Interestingly enough, it has been recently reported that PGE2 induces MMP-9 expression in dendritic cells and that PGE2-induced MMP-9 is required for dendritic cells migration in vivo and in vitro (58). All together, these findings indicate the existence of a close bidirectional association between some MMPs and PTGS2.…”
Section: Discussionsupporting
confidence: 49%
“…COX2 and EP4 have the ability to increase intracellular cAMP levels (28,29), and given their ablated expression upon the loss of virulence, we compared cAMP levels of virulent and attenuated macrophages. Upon attenuation, the amount of intracellular cAMP decreases by almost 50% and can be restored by the addition of TGF-␤2 ( Fig.…”
Section: Expression Of Cox2 Ep4mentioning
confidence: 99%
“…Moreover, PGE 2 is able to induce MMP-9 expression in dendritic cells. 52 After cerebral ischemia, HMGB1 can upregulate MMP-9 expression/activity in neurons and astrocytes, signaling neighboring cells to increase blood-brain barrier permeability and recruit immune cells. 53 We recently reported that HMGB1 inhibition decreases MMP-9 activity, thereby decreasing ICH-induced early brain injury.…”
mentioning
confidence: 99%